Understanding shame, guilt, embarrassment and pride: a systematic review of self-conscious emotions - Singh, Diksha; Bhushan, Braj (Frontiers in Psychology, 2025)
Self-conscious emotions play a crucial role in social functioning, moral behavior, and identity formation. Their inherent complexity, necessitating self-awareness and social evaluation, presents significant challenges for empirical research. This systematic review identifies methodological issues and gaps in experimental research related to the affective traits (valence and arousal), physiological and neural correlates, nonverbal cues, and cross-cultural variations of self-conscious emotions. A comprehensive search was conducted for peer-reviewed empirical studies published between 2000 and 2024 across databases such as PubMed, PsycINFO, Scopus, and Web of Science, adhering to PRISMA 2020 guidelines. Inclusion criteria focused on studies examining self-conscious emotions through physiological, neurological, behavioral, or cross-cultural approaches. A total of twenty-three studies were included, revealing variability in the valence and arousal profiles of self-conscious emotions, with distinct physiological and neural correlates identified in regions such as the medial prefrontal cortex, anterior cingulate cortex, and default mode network. Nonverbal cues, including posture, blushing, and gaze aversion, exhibited differences among emotions. Cross-cultural studies highlighted both universal and culturally specific patterns in the elicitation and expression of these emotions. However, limitations such as challenges in experimental induction, ecological validity, and construct operationalization hinder the generalizability and replicability of findings. The predominance of Western-centric studies further restricts cross-cultural applicability. Overall, self-conscious emotions remain underexplored compared to basic emotions, primarily due to methodological and ethical challenges. Future research should prioritize standardized definitions, ecologically valid designs, multimodal measurements, and diverse cultural samples to deepen the understanding of these complex emotions and their implications in clinical, social, and developmental contexts.